Stability of a 3-variable quadratic functional equation - K. Ravi; M. Arunkumar (Penerbit ukm, 2008)
In this paper, the authors discuss the general solution and the stability of a 3-variable quadratic functional equation f(x+y,z+w,u+v)+ f(x-y,z-w,u-v)= 2f(x, z,u)+ 2f(y,w,v). The quadratic form f (x,y,z)=ax2+by2+cz2+d xy+e yz+f zx is found to be the solution of the above functional equation